Military adaptation in war with fear of change - Murray, Williamson (Cambridge University Press, 2011)
"Military Adaptation in War addresses one of the most persistent, yet rarely examined, problems that military organizations confront: namely, the problem of how to adapt under the trying, terrifying conditions of war. This work builds on the volume that Professor Williamson Murray edited with Allan Millett on military innovation (a quite different problem, though similar in some respects). In Clausewitzian terms, war is a contest, an interactive duel, which is of indeterminate length and presents a series of intractable problems at every level, from policy and strategy down to the tactical. Moreover, the fact that the enemy is adapting at the same time presents military organizations with an ever-changing set of conundrums that offer up no easy solutions. As the British general, James Wolfe, suggested before Quebec: "War is an option of difficulties." Dr. Murray provides an in-depth analysis of the problems that military forces confront in adapting to these difficulties"--